An unusual presentation of a corpus luteum rupture - Parth Godhiwala; Himanshi Agarwal; Sourya Acharya; Neema Acharya; Vivek Lahane (Wolters Kluwer Medknow Publications, 2022)
Rheumatic heart disease (RHD) is one of the most common cardiac conditions seen in India with mitral stenosis as the most prevalent cause affecting females more than males. With the increasing number of patients undergoing mitral valve replacement (MVR) and mandatory use of anticoagulants post-MVR, the patients presenting with drug-induced coagulopathy have increased. One of the rare complications of coagulopathy-related hemorrhage may be associated with a gynecological cause with maximum risk in women of reproductive age group. This chance of hemorrhage has increased due to various events that occur in reproductive organs, namely, ovulation, menstruation, trauma due to sexual intercourse, or pregnancy-related bleeding. Such bleeding is evident as external vaginal bleeding or hemoperitoneum. Hereby, we present a rare case of a 30-year-old woman, on anticoagulant therapy for MVR who presented with congestive cardiac failure associated with massive hemoperitoneum. On ultrasound-guided paracentesis, the cause of mild-to-moderate ascites was normal ovulatory bleed evident by the bleeding from the corpus luteal cyst.